Effects of seasonal and geographical variations on the physicochemical properties of commercial pasteurized milk in the northwest of Iran. Issue 1 (13th February 2017) - Moosavy, Mir-Hassan; Roostaee, Nassim
Abstract : Purpose: The composition and properties of milk are considerably important for dairy farmers, manufacturers and consumers. Despite the significant role of bovine milk in Iranian dairy products, there is little information about the effect of production season and location on the physicochemical properties of pasteurized milk as a final product. The purpose of this study was to investigate the effects of seasonal, geographical and product brand variations on the chemical components and physical properties of Iranian pasteurized bovine milk. Design/methodology/approach: A total of 400 samples of pasteurized milk were obtained during a 12-month period, from April 2014 to March 2015, using random sampling. Chemical components (protein, fat, lactose, dry matter and solids-not-fat) and physical properties (freezing point, extraneous water content, titratable acidity, density and pH) of the collected samples were analyzed. A one-way ANOVA was used to perform the statistical analysis of data, and results were presented as the mean ± standard deviation. Findings: It was found that the biochemical constituents and physical properties of pasteurized milk samples were linked to seasonal and geographical variation parameters. The milk sampled during spring and summer contained significantly less fat, protein and solids-not-fat ( p < 0.05) than samples in autumn and winter. Also, samples in spring had a significantly higher ( p < 0.05) extraneous water (0.8 per cent) compared to milk sampled in winter (−0.4 per cent). Samples in Maragheh and Mianeh contained the highest level of fat (2.82 per cent) and protein (3.09 per cent) content in the province. The sampled milk from the south (Mianeh and Hashtrud) and the northwest (Marand) had also significantly higher ( p < 0.01) freezing points than the other areas. No significant differences ( p > 0.01) were found in physicochemical properties in different product brands of the milk samples. Originality/value: Seasonal and geographical parameters are crucial factors in the diversity of physicochemical parameters of commercial pasteurized milk. In this study, unlike the other studies, differences in milk product brand were not significant. Further research will be needed to assess other factors such as the effect of management practices and feeding strategies on farms.